Beyond the Schools of Psychology 1: A Digital Analysis of Psychological Review, 1894–1903. Issue 2 (20th February 2013) - Green, Christopher D.; Feinerer, Ingo; Burman, Jeremy T.
<x xml:space="preserve">Abstract</x> Traditionally, American psychology at the turn of the twentieth century has been framed as a competition among a number of "schools": structuralism, functionalism, behaviorism, etc. But this is only one way in which the "structure" of the discipline can be conceived. Most psychologists did not belong to a particular school, but they still worked within loose intellectual communities, and so their work was part of an implicit psychological "genre, " if not a formalized "school." In this study, we began the process of discovering the underlying genres of American psychology at the turn of the twentieth century by taking the complete corpus of articles from the journal Psychological Review during the first decade of its publication and conducting a statistical analysis of the vocabularies they employed to see what clusters of articles naturally emerged. Although the traditional functionalist school was among the clusters we found, we also found distinct research traditions around the topics of color vision, spatial vision, philosophy/metatheory, and emotion. In addition, momentary clusters corresponding to important debates (e.g., the variability hypothesis) appeared during certain years, but not others.